Prevalence and predictors of antidepressant prescribing in Northern Ireland - Shevlin, Mark; Rosato, Michael; Boyle, Stephanie; Murphy, Jamie; Boduszek, Daniel (International Journal of Population Data Science, 2018)
Background Antidepressant prescription rates in the United Kingdom (UK) are among the highest in Western Europe and prescription rates in Northern Ireland (NI) are significantly higher than the rest of the UK. Moreover, while prescription rates are climbing annually, rates of depression are not changing, and evidence suggests that a range of socio-economic and geographical factors may be responsible. Objectives The primary aim was to calculate the rates of antidepressant prescribing for the Northern Ireland population for years 2011 to 2015 and identify significant socio-demographic predictors. Methods (including data) This Administrative Research Centre (Northern Ireland) study linked data from the 2011 census and prescribing records (Enhanced Prescribing Database). The British National Formulary codes was used to identify the four main antidepressant drug types. Findings Results indicated high levels of antidepressant prescribing for years 2011 to 2015 and significant associations were found with demographic, health, and economic variables. Conclusions Northern Ireland has high levels of antidepressant prescribing compared to other parts of the UK and other European countries. This suggests that there is a need to extend the provision of social prescribing, where people can avail of local, non-clinical options to alleviate mental health problems.